Bio-oil from biomass fast pyrolysis: Yields, related properties and energy consumption analysis of the pyrolysis system. (15th December 2021) - Li, Pan; Shi, Xiaopeng; Wang, Xianhua; Song, Jiande; Fang, Shuqi; Bai, Jing; Zhang, Guojie; Chang, Chun; Pang, Shusheng
Abstract: Based on a comprehensive study of biomass fluidized bed device, a fast pyrolysis experiment to produce bio-oil was carried out using rice husks as raw material. The effects of reaction temperature, fluidized gas volume, and feed rate on the yield of bio-oil were studied. Experiments showed that the best temperature for bio-oil yield was 500 °C, the best fluidizing gas flow rate was 22 m³/h and the best feed rate was 2.65 kg/h. The physical and chemical properties of bio-oil were analyzed, and the results showed that the density, acidity, calorific value, and viscosity of the first-level bio-oil were greater than those of the second-level bio-oil. Among the components, the contents of acids (18.74%), ketones (22.51%), esters (16.90%), and phenols (17.91%) were relatively high. Aspen Plus software was used to analyze the energy consumption of the reaction model. Most of the energy in the fast pyrolysis of biomass is consumed for the preheating and cooling of nitrogen, which accounts for 60% of the total energy consumption. The combustion of the coke and non-condensable gas, which are produced as by-products can be used for preheating raw materials to realize self-heating production. Combine experiment and simulation will promote its industrialization. Graphical abstract: Image 1 Highlights: First-level bio-oil, suited for boiler combustion, has calorific value of 16.3 MJ/kg. Bio-oil yield was analyzed using the control variable method. Preheating and cooling of nitrogen accounts for 60% of the total energy consumption. By-products meet requirements to realize the net energy output of bio-oil.